Psychosocial risk and work decisions of transport workers: A study - Agnieszka Mościcka-Teske; Joanna Sadłowska-Wrzesińska; Brigita Gajsek; Agnieszka Stachowiak (Journal of Sustainable Development of Transport and Logistics, 2023)
Purpose: The main objective of the research was to identify the structure and level of psychosocial risk experienced by transport workers and the relation between occupational stress and the decision to leave the job. Methodology: The research on psychosocial risks at work and their impact on job-related decisions was conducted with the Psychosocial Risk Scale (SRP), a scientifically verified diagnostic tool characterized by high reliability and accuracy of coefficients. The scale consists of four parts, A, B, C, and D. Part A concerns demographic data (such as age, gender, seniority, position, etc.). Part B contains questions related to health and professional functioning. Part C consists of 50 statements related to characteristics of work that pose potential psychosocial risks. Annex D-SRP for the transport sector contains 12 questions (α-Cronbach factor = 0.80). Psychometric properties of parts B and C of the Psychosocial Risk Scale were determined on the basis of the survey results. Results: The psychosocial risk categories considered were workload, job content, work schedule, control, environment and equipment, organizational culture and function, interpersonal relationships, career development, and work-life interface. The mediating effect of job satisfaction was also considered to provide a holistic perception of the analyzed problem. Job satisfaction was analyzed in job content, work conditions and organization, financial conditions, career development, and interpersonal relations with superiors and co-workers. Based on research results, authors identified and characterized the impact of psychosocial risk on transport workers' job-related decisions. Theoretical contribution: The research links social sciences, psychology, and management studies exploring the links between occupational stress and HR management implications, filling in a research gap between occupational stress and logistics management and creating new gaps and research questions as conclusions from research open following research fields and opportunities in the context of research on sustainable development of enterprises. It adds a new perspective to transport management, proving that risk resulting from job characteristics and organization can compromise the availability of workers and the quality of processes performed. Practical implications: The research results can be used by HR managers and workload planners to minimize the occupational stress experienced and improve the well-being and performance of transport workers.